Cellular Mechanisms of Saline Extract of Alligator Pepper (Zingiberaceae Aframomum melegueta) for Specific Protection against Preeclampsia - Inegbenebor, Ute; Ebomoyi, Maureen (Journal of Nutritional Therapeutics, 2014)
Preeclampsia is a clinical syndrome defined as the new onset of hypertension and proteinuria during the second half of pregnancy. Though it is easily diagnosed clinically, affected persons must book in a health service facility for the diagnosis to be made. Furthermore regular screening is necessary during several antenatal visits and skilled attendant’s supervised labor before diagnosis can be made. Predictive tests are not yet well developed and not readily available in developing countries and medically underserved areas where they are needed most. There is therefore a need for specific protection against preeclampsia to be developed. This will ensure that all women are protected even when they choose not to visit an antenatal clinic. Specific protection is potentially capable of preventing preeclampsia in 5 % to 7% of pregnant women, the proportion of pregnant women that are affected by preeclampsia worldwide. This article builds on a previous article on the study of the cellular mechanisms underlying gestational weight gain and litter weight reduction effect of aqueous extract of Alligator pepper and attempts to analyze how the anti-hyperinsulinemic property of the constituents of Alligator pepper in that study can also prevent preeclampsia and suggests the use of some of the constituents of alligator pepper as specific protection (vaccine) for the prevention of preeclampsia.